Condition of the Gastrointestinal Tract in Rheumatological Patients - Сибиркина Марина Валерьевна (Scholars Digest Publishing, 2023)
In rheumatological practice, nonsteroidal anti-inflammatory drugs (NSAIDs) remain of great importance in the treatment of rheumatoid arthritis (RA), ankylosing spondylitis (AS), osteoarthrosis (OA), gout, etc., the widespread use of which is due to the relief of pain and inflammation, which are the main clinical manifestations of rheumatological diseases (RH). At the same time, it is reliably known that regular use of NSAIDs is associated with a number of side effects and risks, the leader of which is inflammatory, erosive, and ulcerative changes in the mucous membrane of the gastrointestinal tract (GIT) [13, 14]. One of the unresolved issues is the occurrence of secondary damage from the gastrointestinal tract (GI).
Keywords: rheumatological diseases, gastrointestinal tract, NVPP, corticosteroids, apoptosis, proliferation, gastric mucosal epithelial cells.